THE IMPORTANCE OF THE RURAL ADMINISTRATOR IN THE PROCESS OF COMPANY MANAGEMENT, PROPERTY AND PRODUCTION - Puzzi, Diogo Mazzo; Magrini, Rosemary Chiuchi (Revista Interface Tecnológica, 2022)
The context of People Management is formed by people and organizations. These people are characteristic for companies as human capital, where they should invest, and seek a good return for the company, in addition to personal motivation. The theme of this study is to understand the importance of having a rural administrator, in the process of managing the company, property and production. How they perform tasks so that it can lead to the proper functioning of the institution with humanization and satisfaction of its client and its employees. Through the general objective, it showed that rural management is important for the good performance of the agricultural segment. The study hypothesis was confirmed to the extent that the survey results showed that it is necessary to use management tools for controls and relationships with customers and employees. This study is of an exploratory nature since it helps the researcher to solve and/or increase his expectation according to the problem determined. Finally, it is concluded that the discussion through the authors and the investigation through the application of interviews, thus presenting the need of the administrator in its production or property.
Keywords: Agribusiness; Agricultural; People Management; Human Resources